2020
DOI: 10.1186/s40069-020-00407-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Assessment of Flexural and Shear Behavior of Precast Prestressed Deep Hollow-Core Slabs

Abstract: The paper presents the results of flexural and shear tests up to failure on full-scale hollow-core slabs (HCS) having a depth of 500 mm. A detailed non-linear 2D finite element model is also developed to predict the stress distribution and crack pattern within the slabs, providing a well match with experimental results. Experimental and numerical results are compared with analytical calculations provided by Product Standard EN 1168, highlighting the inaccuracy of technical regulations in predicting shear behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A relevant difference between the code predicted shear strength (EN 1168) and the experimental test results for 500 mm thick slabs was also observed by Michelini et al [19]. The authors also carried out non-linear 2D finite element model to predict the stress distribution and crack pattern within the slabs, obtaining a good match with experimental results.…”
Section: Introductionmentioning
confidence: 75%
“…A relevant difference between the code predicted shear strength (EN 1168) and the experimental test results for 500 mm thick slabs was also observed by Michelini et al [19]. The authors also carried out non-linear 2D finite element model to predict the stress distribution and crack pattern within the slabs, obtaining a good match with experimental results.…”
Section: Introductionmentioning
confidence: 75%
“…As observed, few studie investigated the behavior of Steel-Concrete composite beams with PCHCS Tawadrous and Morcous [4] and El-Sayed et al [5] showed that, due to the succes of PCHCSs, deeper HCUs were developed to resist higher loads and to support spans. In this scenario, some researchers carried out tests to investigate the beha deeper PCHCSs [12,13,[27][28][29][30][31][32]. However, these investigations did not consider com behavior, i.e., Steel-Concrete composite beams.…”
Section: Numerical Model: Validation Studymentioning
confidence: 99%
“…When applied to structures, there should be continuity between the slab ends so that the entire floor engages in diaphragm action. For the hollow core slabs with topping concrete, interfaces must be structurally assessed to prevent sliding failure in the horizontal direction, so as to allow composite cross sections to exhibit the expected structural performance [ 3 , 8 , 17 , 18 , 19 , 20 , 21 ]. In push-off tests with manufacturing method and interface roughness as variables, Mones and Breña (2013) [ 3 ] found that horizontal shear strength evaluation was significantly influenced by the presence of laitance, the interface roughness, and the direction.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies [ 3 , 8 , 17 , 18 , 19 , 20 , 21 , 22 ], most researchers have examined the shear capacity of the HCS with topping concrete in terms of interface roughness. The HCSs are manufactured such that the roughness applied to the upper surface is in the direction of product width (horizontal) in order to secure shear strength.…”
Section: Introductionmentioning
confidence: 99%